2020
DOI: 10.3382/ps/pez496
|View full text |Cite
|
Sign up to set email alerts
|

A novel Bacillus based multi-strain probiotic improves growth performance and intestinal properties of Clostridium perfringens challenged broilers

Abstract: There is a necessity for the implementation of in-feed probiotics in the poultry production industry, following strict regulations around the use of antibiotic growth promoters ( AGP ). Bacillus spp. are becoming an attractive alternative because of their functionality and stability. This study aims to evaluate the effect of a novel multi-strain Bacillus based probiotic on growth performance and gut health in male Ross 308 broiler chickens ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 51 publications
(25 reference statements)
5
49
0
3
Order By: Relevance
“…It is thus evident that the alternative additives did not compromise the weight of broilers in the starter phase, as opposed to broilers that did not receive any additives, which presented lower body weight. This is consistent with the results of He et al 2019, Min et al (2016), Ramlucken et al (2020), and Zang et al 2014, who reported beneficial effects of probiotics and synbiotics on the performance of broilers in the starter phase. It must be noted that the imposed sanitary challenge, i.e., reusing litter without treatment, only weekly cleaning of pendular drinkers, and providing water without chlorine, affected birds in the starter phase, which represents the period when the animal immune system is still developing.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is thus evident that the alternative additives did not compromise the weight of broilers in the starter phase, as opposed to broilers that did not receive any additives, which presented lower body weight. This is consistent with the results of He et al 2019, Min et al (2016), Ramlucken et al (2020), and Zang et al 2014, who reported beneficial effects of probiotics and synbiotics on the performance of broilers in the starter phase. It must be noted that the imposed sanitary challenge, i.e., reusing litter without treatment, only weekly cleaning of pendular drinkers, and providing water without chlorine, affected birds in the starter phase, which represents the period when the animal immune system is still developing.…”
Section: Resultssupporting
confidence: 93%
“…He et al (2019) reported better performance and greater production of immunoglobulins in broilers fed diets containing Bacillus subtilis. Similarly, Ramlucken et al (2020) reported that B. subtilis and Bacillus velezensis produce exogenous enzymes, improving nutrient utilization and feed conversion in supplemented animals.…”
Section: Introductionmentioning
confidence: 98%
“…Overall, groups of male Ross 708 broilers administered B. subtilis supplementation had total body weight gain averaging 553 g, comparable to AGP supplementation average of 563 g with all groups outperforming the challenged control (493 g) [ 189 ]. Ramlucken et al, when testing a selective multi-strain Bacillus probiotic mixture of B. subtilis CPB 011, CPB 029, HP 1.6, and D 014, and B. velezensis CBP 020 and CPB 035, noted improved feed conversion ratio, increased body weight gain, and overall improved performance compared to unsupplemented and commercial Bacillus supplemented flocks when challenged with C. perfringens [ 190 ]. Probiotics may also promote economic savings of $0.018 USD/kg of body weight when B. subtilis was included in a two percent reduced metabolizable energy diet [ 191 ].…”
Section: Disease Prevention Strategies In Naementioning
confidence: 99%
“…DFMs are viable, naturally occurring microbial cultures, including bacteria belonging to the genera Lactobacillus, Enterococcus, Streptococcus, Bifidobacterium, and Propionibacterium, which when fed to the host animal, generate a beneficial health response through their ability to modulate the diversity and composition of the gut microbiota. Various species of Bacillus also have been tested as DFMs on the basis of their ability to inhibit pathogens by producing antimicrobials (13)(14)(15). Bacillus has the added advantage as a DFM of producing spores that are resistant to low pH, bile salts, and other harsh conditions of the gastric environment (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%